Dynamic interplay between RNA N 6-methyladenosine modification and porcine reproductive and respiratory syndrome virus infection - Zi-Han Wang; Jing Li; Sai-Ya Ma; Meng-Xuan Liu; Yu-Fei Zhan; Feng Jin; Bing-Xin Liu; Wenjing Wang; Mei He; Yu-Chuan Yang; Yandong Tang; Peng Wang; et al. (Veterinary Research)
Abstract N 6 -methyladenosine (m6A) has attracted significant attention for its role in regulating the complex interaction between viruses and host cells. Porcine reproductive and respiratory syndrome virus (PRRSV) is a significant pathogen affecting swine health worldwide. Here, we first identified seven m6A-enriched peaks in PRRSV genomic RNA by m6A RNA immunoprecipitation sequencing (m6A-seq). Moreover, functional analyses revealed a positive correlation between the m6A modification level and PRRSV replication. Treatment with the universal methylation inhibitor 3-deazaadenosine (3-DAA) effectively suppressed PRRSV replication in a dose-dependent manner. Furthermore, m6A-seq was also used to determine the m6A landscape of the transcriptome in PAMs infected with pandemic or highly pathogenic PRRSV strains. Among the 4677 transcripts exhibiting altered m6A modification levels, the MAPK14 gene and the p38/MAPK signalling pathway emerged as preliminary targets of m6A-mediated epigenetic regulation during PRRSV infection. These findings provide new insights into the epigenetic mechanisms underlying PRRSV infection and may facilitate the development of anti-PRRSV therapeutics.